Dietary omega-3 polyunsaturated fatty acids and fish intake and risk of age-related macular degeneration. Issue 12 (December 2021) - Jiang, Hong; Shi, Xin; Fan, Yahui; Wang, Duolao; Li, Baoyu; Zhou, Jin; Pei, Cheng; Ma, Le
Summary: Background & aims: Epidemiologic studies are inconsistent regarding the association of dietary omega-3 polyunsaturated fatty acids (PUFA) and/or fish intake with risk of age-related macular degeneration (AMD) incidence and progression. The objective was to determine these associations by conducting a meta-analysis of available studies. Methods: Three electronic databases were searched for studies that quantified dietary omega-3 PUFA and/or fish intake from inception to December 2020 without language restriction. Three investigators independently assessed for inclusion and extracted data. Study-specific risk estimates were combined using random-effects model. Potential dose–response associations were explored with the use of generalized least-squares trend estimation. Results: 21 studies were included in the meta-analysis. Higher dietary intakes of omega-3 PUFA was significantly associated with 14% (relative risk [RR]: 0.86, 95% confidence interval [CI]: 0.77, 0.96) and 29% (RR: 0.71, 95% CI: 0.55, 0.91) lower risk of early and late AMD, respectively. The dose–response analysis showed a 6% and 22% decrease in the risk of early and late AMD for each additional 1 g/d omega-3 PUFA intake. For individual omega-3 PUFA, the intake of eicosapentaenoic acid and docosahexaenoic acid was inversely associated with lower AMD risk, whereas no association was found for the alpha-linolenic acid. Consistent inverse associations were also found between fish intake and AMD. The pooled RRs comparing extreme categories of fish intake were 0.79 (95% CI: 0.70, 0.90) and 0.71 (95% CI: 0.60, 0.85) for early and late AMD risk, respectively. Every 15 g/d of fish consumption was associated with 13% and 14% lower early and late AMD. In addition, fish intake was associated with a significantly reduced risk of AMD progression (RR: 0.73, 95% CI: 0.53, 1.00). Conclusions: A high intake of dietary omega-3 PUFA or fish was associated with a reduced risk of developing of AMD, which further supports that consumption of omega-3 PUFA-rich foods may be a new avenue nutritional approach to preventing AMD.